The role of care-giving in the well-being of the older persons in Kirinyaga County, Kenya - Murage, Beth Wangithi; Warutere, Peterson Njogu; Mugo, Judy Wairimu (International Journal Of Community Medicine And Public Health, 2021)
Background: The population of the older persons is increasing steadily worldwide. This is secondary to lower fertility rate and increasing longer life. With the increased older person’s population, societies get challenges taking care of the health function of older people. The growth in older person’s population comes with the challenges of taking care of the older persons. As old age sets in, quality of life goes down. Methods: Population based cross-sectional descriptive study was used. Multi-stage sampling method was applied to select participating units starting with Sub County, wards, and then villages. Households with an older person were selected and formed a sampling frame. Systematic random sampling using the sampling frame formed was used at household level to select 333 participating respondents. In case a house hold had more than one older person the eldest or the head of the household/bread winner was selected. Statistical package for social sciences version 25 was used for data analysis. Descriptive analysis was used for social-demographic characteristics. Testing the association between independent variables and dependent variables was done using Chi-square and Odds ratio. Results: The results indicated that age of the older persons respondents (p=0.0001), education (p=0.046), walking with support (p=0.001) and occupation (p=0.020) were significantly associated with care giving in personal hygiene practices. Most of respondents 100 (30.0%) carried out daily activity by themselves, equally by the relative especially on bathing 182 (54.7%) and attending medical appointments 107 (32.1%). Conclusions: The role of care giving in enhancing well-being of the older persons was hygiene, nutrition, environment and older persons abuse whereby feeding and older persons abuse were the most significant.